2003
DOI: 10.1007/bf03021034
|View full text |Cite
|
Sign up to set email alerts
|

Using a personal digital assistant enhances gathering of patient data on an acute pain management service: a pilot study

Abstract: P Pu ur rp po os se e: : Handheld computer technology provides a unique opportunity for health care professionals to access real time or near real time patient information and evidence-based resources at the point-of-care. The purpose of this study was to assess one physician's experience using acute pain assessment software on a personal digital assistant (PDA) to assess patients on an acute pain management service (APMS).M Me et th ho od ds s: : Using a historical control and a "time and motion" study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…8 Another US study on an anaesthetic service showed that a PDA was more effi cient, in terms of time taken and data completeness, in collecting data, than pen and paper. 9 Studies undertaken in developing countries showed similar results. In a study in 2002 on malaria in Gabon, there was a low rate of discrepancies (1.7%) between data entry errors on PDAs and those on paper forms.…”
Section: Data Collection Process At Community Health Centressupporting
confidence: 71%
“…8 Another US study on an anaesthetic service showed that a PDA was more effi cient, in terms of time taken and data completeness, in collecting data, than pen and paper. 9 Studies undertaken in developing countries showed similar results. In a study in 2002 on malaria in Gabon, there was a low rate of discrepancies (1.7%) between data entry errors on PDAs and those on paper forms.…”
Section: Data Collection Process At Community Health Centressupporting
confidence: 71%
“…These tools can be used to obtain real-or near-realtime information on patients' symptom experiences that health professionals may otherwise not have immediate access to [3,57]. Furthermore, they can also potentially be used to detect symptom problems earlier [6] and to improve communication and collaboration around symptom management [24,55].…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors failed to quantify the encounter time advantage, improvements in clinical encounter efficiency for anesthesiology residents using a CDSS for acute pain assessments was noted. 14, 28 The authors suggested that the time advantage benefit associated with PDA implementation justifies their increased use among medical residents.…”
Section: Information Management and Patient Carementioning
confidence: 99%